2009
DOI: 10.1177/1049732308330467
|View full text |Cite
|
Sign up to set email alerts
|

Between Being Cured and Being Healed: The Paradox of Childhood Cancer Survivorship

Abstract: In this article, we describe how young adults who are transitioning off treatment for childhood cancer and beginning early survivorship are living in what might be described as a paradox of reality. These survivors' dual reality is their experience of intense frustration with their current state of functioning, and an overwhelming relief that therapy is over and that they survived. They have feelings of fear, trepidation, and anxiety for what experiences lay ahead, but have hope for the future. Finally, they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
77
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 19 publications
1
77
0
Order By: Relevance
“…The majority of the studies included both males and females. [24][25][26][27][28][29][30][31][32][33][34] Three studies did not indicate the gender distribution, [35][36][37] and the remaining two studies reported the inclusion of either all females 38 or all males. 39 The age of participants included in the studies ranged from 13 to 38 years old at the time of interview.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the studies included both males and females. [24][25][26][27][28][29][30][31][32][33][34] Three studies did not indicate the gender distribution, [35][36][37] and the remaining two studies reported the inclusion of either all females 38 or all males. 39 The age of participants included in the studies ranged from 13 to 38 years old at the time of interview.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Although YASCC greatly desire to become part of the mainstream or peer groups, 28,35 they reported difficulty in fitting in and consequently experienced feelings of loneliness and isolation. 35 Survivors noted how missing out on developmentally important milestones caused them to be either more 38 or less mature 33 than their peers, which for some consequently affected their ability to assimilate with peer groups. 38 YASCC also reported being stigmatized by their peers due to their physical impairments, 26 and some purposely avoided treatment to hide their disease.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations